1998
DOI: 10.1159/000014335
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control and Hemodynamic Changes in Patients on Long Time Dialysis Treatment

Abstract: In dialysis patients blood pressure can be well controlled with long dialysis (3 times a week for 8 h) in contrast to a more common short dialysis regime (3 times a week for 4 h). We studied whether the good blood pressure control in patients on long dialysis as compared to patients on short dialysis was associated with a decrease in extracellular fluid volume. Two-day interdialytic ambulatory blood pressure monitoring was performed in 26 non-diabetic patients on long dialysis, in 22 patients on short dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…[7][8][9] Hemodynamic changes accompanying to the ultrafiltration performed to prevent hypervolemia are also among well-studied subjects. [10][11][12][13] Also in our study, with a mean amount of ultrafiltration of 2.49 ± 0.83 L performed, significant reduction was observed in post-dialysis systolic blood pressure, diastolic blood pressure and mean arterial blood pressure (113.20 ± 18.57 mmHg, 68.05 ± 11.82 mmHg, 83.10 ± 13.34, respectively) compared to pre-dialysis systolic blood pressure, diastolic blood pressure and mean arterial blood pressure (132.43 ± 17.30 mmHg, 77.10 ± 9.66 mmHg and 95.54 ± 11.41, respectively). Namely, there is a negative significant correlation between ultrafiltration and blood pressure measurements (p50.01).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Hemodynamic changes accompanying to the ultrafiltration performed to prevent hypervolemia are also among well-studied subjects. [10][11][12][13] Also in our study, with a mean amount of ultrafiltration of 2.49 ± 0.83 L performed, significant reduction was observed in post-dialysis systolic blood pressure, diastolic blood pressure and mean arterial blood pressure (113.20 ± 18.57 mmHg, 68.05 ± 11.82 mmHg, 83.10 ± 13.34, respectively) compared to pre-dialysis systolic blood pressure, diastolic blood pressure and mean arterial blood pressure (132.43 ± 17.30 mmHg, 77.10 ± 9.66 mmHg and 95.54 ± 11.41, respectively). Namely, there is a negative significant correlation between ultrafiltration and blood pressure measurements (p50.01).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in salt-sensitive patients, volume control alone fails to reduce blood pressure or left ventricular hypertrophy associated with hypertension, [12][13][14] while the reduction of the dialysate Na concentration combined with dietary salt restriction over several weeks may result in a decrease in the blood pressure, without additional changes in the dry weight. [15] Moreover, it was shown that the volume removal during dialysis is not significantly affected by changes in the dialysis Na concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Measures that are used to determine dry weight include: clinical parameters, especially hypotension or muscle cramps at the end of dialysis [1], normotension at the beginning of dialysis [2,3,4], plasma atrial natriuretic polypeptide (ANP) and cyclic guanosine monophosphate (cGMP) [5], echocardiographic measurement of the inferior vena cava diameter after dialysis [6], and conductivity methods (bioimpedance) [7]. None of these methods seems to be accurate enough [1, 8].…”
Section: Introductionmentioning
confidence: 99%